Penerapan Moderasi Beragama Di Masyarakat Studi Kasus Di Gg Rambutan Sangatta Utara - Nuraini, Juwita Sari; Syakirah, Jihan (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the application of religious moderation in the Rambutan Gg neighborhood, North Sangatta, as an important approach to maintaining harmony in a multicultural society. The aim is to understand the practice of religious moderation and the factors that support or hinder it in daily life. Qualitative methods were used through observation, in-depth interviews, and documentation, allowing for direct data collection from the community and religious leaders. The results indicate a high level of tolerance and harmony between religious communities around the Al Hidayat Mosque and Bethany Church, with concrete examples such as interfaith participation in religious activities such as the sacrifice and Christmas. Supporting factors include the awareness of community leaders and an established culture of tolerance, although obstacles remain such as low religious literacy, the lack of participation of the younger generation in interfaith dialogue, and socio-economic inequality. Handling social media that spreads religious hoaxes is also a significant challenge. Joint efforts are needed to ensure the growth and strengthening of religious moderation in the community.